THE IMPORTANCE OF THE DEVELOPMENT OF THE SERVICE SECTOR IN THE REPUBLIC OF UZBEKISTAN - Xudayberdiyeva Dilafruz Abidovna (American Journals, 2022)
The sphere of services is a generalized category, which includes various types of services, production, provided by enterprises, organizations, as well as individuals.This article shows that the role of the services market as one of the most important sectors of the economy today. The complexity of services and the saturation of the market with new goods require rapid growth of scientific and technological progress, and the article also shows the ways of development of the service sector.
Keywords: services, service sector, social sphere, digital economy, national economy